Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Kantor Imigrasi Kelas II Singaraja - Ni Putu Aprillia Kanaya Putri; Ni Made Dwi Ariani Mayasari (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
Employee performance is a critical factor in determining organizational effectiveness, particularly in public sector institutions that deliver direct services to the community. This study aims to examine the influence of work motivation and work discipline on employee performance at the Class II Immigration Office of Singaraja. A quantitative approach with a causal-associative design was employed. Data were collected through structured questionnaires distributed to all employees using a saturated sampling technique. Work motivation and work discipline were treated as independent variables, while employee performance served as the dependent variable. The data were analyzed using multiple linear regression, supported by classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests.  The results demonstrate that work motivation and work discipline simultaneously have a significant effect on employee performance. Partially, work discipline exhibits a positive and significant influence, indicating that adherence to organizational regulations, punctuality, and responsibility in task execution contribute to improved performance. Conversely, work motivation shows a significant negative effect, suggesting that the existing motivational mechanisms have not been optimally aligned with employees’ expectations and job demands. These findings imply that efforts to enhance employee performance should prioritize strengthening work discipline and reformulating motivational strategies that are more responsive to employees’ needs and organizational goals. This study offers practical implications for human resource management in public sector institutions, particularly in improving service quality within immigration offices.